2020
DOI: 10.1016/j.marpolbul.2020.111097
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from an intercalibration exercise on the quantification and characterisation of microplastic particles in sediment and water samples

Abstract: An intercalibration exercise on the characterisation of microplastics in marine sediment and water samples was carried out among five laboratories involved in the implementation of the Marine Strategy Framework Directive (MSFD) in their country. The samples were prepared by mixing cleaned natural sediment and sea water with microplastics sets made of particles of various polymers, shapes and colours. Overall, the errors on total counts were under 25% in absolute value. The risk of non-detection and loss of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Microplastic visual screening varies with individual experience and the particular shapes, sizes and colours of MP particles (Cadiou et al, 2020). MP screenings under microscopy should aim to be conservative and carried out blind, in a randomized order, with a pre-determined and standardized search time and search criteria to reduce bias and variation in counts.…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Microplastic visual screening varies with individual experience and the particular shapes, sizes and colours of MP particles (Cadiou et al, 2020). MP screenings under microscopy should aim to be conservative and carried out blind, in a randomized order, with a pre-determined and standardized search time and search criteria to reduce bias and variation in counts.…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…The implementation of the MSFD in the EU countries was an important driver for increasing the number of studies in European waters on this issue. Although the methods used for sampling and analysis have already been reviewed (see e.g., Hidalgo-Ruz et al 2012;GESAMP 2019), differences between the studies highlighted the need to improve standardization by defining simple, effective, and reproducible methods (Cadiou et al 2020;Prata et al 2019;Maes et al 2019;Cowger et al 2020). Related to the establishment of a monitoring program for MPs in the marine environment, the environmental indicators should have the following characteristics (see e.g., UNEP 2016);…”
Section: Global Monitoring: Gaps and Challengesmentioning
confidence: 99%
“…While particle counting, estimation, and identification technology has advanced considerably in recent years, the manual work of analysts remains essential for the foreseeable future, but represents a critical source of analytical deviation and error. A recent critical review focused on quality criteria for the analysis of MPs in biota samples (Hermsen et al 2018), while an intercalibration exercise on MP characterization and quantification in sediment and water samples has also been published recently (Cadiou et al 2020). In this last study, the authors reported a 25% deviation in the interlaboratory exercise, mainly due to underestimation of the methodological processes, the risk of losing MP with the applied extraction methods, and human error in particle counting.…”
Section: Global Monitoring: Gaps and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 A few studies have been conducted to compare results among measurement methods. [22][23][24][25][26] In addition, several groups, including the Japanese Ministry of the Environment on behalf of an international consortium, have published standardized methods. 27,28 However, those efforts have been focused on single or limited media, such as seafood or the water column, or have focused on only a subset of required standardization activities, such as field collection methods, microplastics extraction, or measurement technology.…”
Section: Research Gapsmentioning
confidence: 99%